Turning strawberry jam into slice: a new way of consuming strawberry fruits preservation products. Issue 1 (March 2021) - Wahyuningtias, D; Caroline, A; Adiati, M P; Levyta, F; Kusumawardhana, I
Abstract: The goal of this article is to discover an acceptance and preference of consumer towards innovative products of slice strawberry jam. While an ordinary fruit preserves often made as a jam. Sliced jam is a new way of fruit preservation to consume. Through an organoleptic study, the paper starts to examine and compare between an original product of strawberry jam to sliced jam. A quantitative tradition of research employs an experimental approach to eighty untrained respondents. Data analysis and validity were generated from SPSS statistic software to measure the result of questionnaires towards a favorite between the two and its characteristics such as texture, taste, smell, and color. The findings reveal that the new form of strawberry jam slices is favored among the major respondents. The strawberry jam slice's texture, taste, smell, and color also attract the consumerism. Despite the limitation of the study, the article introduces a new way of consuming strawberry fruits preservation products. Thus, the research discussion would take forward business development idea, particularly on fruit preserves preparation.